Determinants of Behavioral Adoption in Influencer Marketing Platforms: The Roles of Perceived Ease of Use, Usefulness, Satisfaction, and Trust - Thivanka Chamith Wijesinghe (Management Science Research Journal, 2026)
Influencer marketing has become a dominant strategy for engaging consumers on social media platforms such as TikTok, Instagram, and YouTube. This study investigates the factors that drive users’ behavioral adoption of influencer-driven content and platforms, drawing on the Technology Acceptance Model (TAM) and its extensions. Building on a review of influencer marketing literature and empirical analysis, the research examines the relationships among Perceived Ease of Use (PEU), Perceived Usefulness (PU), Satisfaction (S), Trust (T), and Behavioral Adoption (BA). Results reveal that PEU exerts the strongest influence on BA, indicating that intuitive interfaces and low complexity are critical to encouraging adoption. Satisfaction emerges as the second-most significant factor, suggesting that positive user experiences foster ongoing engagement. PU also contributes to adoption, though its effect is weaker than that of PEU. Trust shows a moderate but meaningful impact, underscoring the importance of credibility and security in sustaining long-term participation. These findings provide practical guidance for marketers and platform designers seeking to enhance user acceptance of influencer-based campaigns.